Impact of COVID-19 on Pakistan’s services sector - Asif Javed (Jurnal Inovasi Ekonomi, 2020)
Coronavirus disease 2019 (COVID-19) affects the world economies as due to pandemic major economic activities are either suspended or restricted. Pakistan also faces the similar circumstances as implementation of lockdown to avoid spread of COVID-19 halted trading activities. This study focuses on the impact of COVID-19 on services sector of Pakistan and for the purpose various published reports are considered. Sectors including tourism, hospitality and transport are likely to be more affected in services sector. Millions of SMEs may not be able to survive in long term due to lack of cash flow while the revenues of SMEs will also decrease. Lockdown situation will give rise to the vulnerable employment and the layoffs in every province of Pakistan are expected. This paper recommends that entrepreneurial-based programs effectively create jobs, especially by promoting information technology and e-commerce.